Strange Syntax: The Use of Foreign Languages in American Musicals. - Sircus, Kyle Matthew. (Tufts Archival Research Center, 2005)
The American musical has long been regarded as a cultural document, whose reflexive relationship with American society allows us to glean much about our national and personal identities. How then do foreign languages integrate themselves into a distinctly American form (heavily influenced by immigrants) and reflect a contemporary outlook on American culture? Does telling a story in more than one language impact an audience's comprehension of or engagement with a show? Against the backdrop of uses of foreign languages in American immigrant performance from the late nineteenth to mid-twentieth century, I explore the use of four African dialects in the stage adaptation of The Lion King (1998) and how Spanish is integrated into the narrative of In the Heights (2008). For each show, I rely on close readings of lyrics and dialogue, primary source documents published about each production, archival materials from rehearsals, and my personal interviews with theatre historians and the creators themselves. In my examination of two musicals that seem completely antithetical, I analyze the use of language in the narrative itself; the effects of second language use on the audience's comprehension; and finally how the language hybridity of each show affects its assimilation into the Broadway oeuvre.